Federalism and optimal allocation across levels of governance - Benny Geys; Kai A. Konrad (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2010)
Countries differ in their governmental architectures and in the rules that describe the allocation of tasks, rights and duties across the various levels of government. In this paper, we present a short and selective survey of the development of the theory of optimal allocation of rights and duties along the vertical dimension in federations. We thereby first discuss the multiple trade-offs brought forward in the literature; these make that an ideal allocation of actual tasks across levels of government may be difficult, if not impossible, to attain. Then we turn to the consequences of a sub-optimal allocation of tasks and discuss spillover effects, strategic interactions between jurisdictions and intergovernmental competition. Throughout the review, we highlight paths in need of further research such that, in time, we will have a more solid ground for policy advice. – – Staaten unterscheiden sich hinsichtlich ihres Regierungsaufbaus und ihren Verteilungsregeln von Aufgaben, Rechten und Pflichten über die verschiedenen Regierungsebenen hinweg. In diesem Artikel stellen wir eine kurze und selektive Übersicht über die Entwicklung der Theorie der optimalen Allokation von Rechten und Pflichten entlang der vertikalen Dimension in Staatenbünden vor. Wir diskutieren dabei zuerst die vielfachen, in der Literatur beschriebenen, Trade-offs. Diese führen dazu, dass eine ideale Verteilung der tatsächlichen Aufgaben schwierig, wenn nicht unmöglich zu erzielen ist. Als nächstes wenden wir uns den Konsequenzen der sub-optimalen Aufgabenverteilung zu und diskutieren externe Effekte, strategische Interaktionen zwischen den verschiedenen Gebietskörperschaften und zwischenstaatlichen Wettbewerb. Im gesamten Überblicksartikel stellen wir mögliche Pfade für notwendige weitere Forschung heraus, mit der für die Zukunft eine solide Grundlage für Politikberatung gelegt werden kann.
Keywords: 330